Effects on the trade and non-traded sectors - Kai Leitemo; Øistein Røisland (University of Oslo, Department of Economics, 1999)
The paper considers alternative monetary policy regimes within a calibrated macroeconomic model with a traded and a non-traded sector. Two classes of regimes are considered; inflation targeting and exchange rate targeting. When the target variable is completely stabilized, both rules have poor stabilizing properties for all real variables - nominal exchange rate targeting is even dynamically unstable. When the monetary authority places some weight on output stabilization in addition to the primary target variable, inflation targeting outperforms exchange rate targeting in terms of output stability in both the traded and the non-traded sectors.
Keywords: 330; Geldpolitik; Inflation Targeting; Wechselkurspolitik; Nicht-handelbares Gut; Handelbares Gut; Theorie; Theorie